Primary prevention of food allergy in children and adults: systematic review. Issue 5 (16th January 2014) - de, D.; Geromi, M.; Halken, S.; Host, A.; Panesar, S. S.; Muraro, A.; Werfel, T.; Hoffmann‐Sommergruber, K.; Roberts, G.; Cardona, V.; Dubois, A. E. J.; Poulsen, L. K.; et al.
Abstract Background Food allergies can have serious physical, social, and financial consequences. This systematic review examined ways to prevent the development of food allergy in children and adults. Methods Seven bibliographic databases were searched from their inception to September 30, 2012, for systematic reviews, randomized controlled trials, quasi‐randomized controlled trials, controlled clinical trials, controlled before‐and‐after studies, interrupted time series studies, and prospective cohort studies. Experts were consulted for additional studies. There were no language or geographic restrictions. Two reviewers appraised the studies using appropriate tools. Data were not suitable for meta‐analysis due to heterogeneity, so were narratively synthesized. Results Seventy‐four studies were included, one‐third of which were of high quality. There was no good evidence to recommend that pregnant or breastfeeding women should change their diet or take supplements to prevent allergies in infants at high or normal risk. There were mixed findings about the preventive benefits of breastfeeding for infants at high or normal risk, but there was evidence to recommend avoiding cow's milk and substituting with extensively or partially hydrolyzed whey or casein formulas for infants at high risk for the first 4 months. Soy milk and delaying the introduction of solid foods beyond 4 months did not have preventive benefits in those at high or normal risk. There was very little evidence about strategies for preventing food allergy in older children or adults. Conclusions There is much to learn about preventing food allergy, and this is a priority given the high societal and healthcare costs involved.